ANALISIS PRODUKTIVITAS KERJA KAJIAN IMPLIKASI BUDAYA PERUSAHAAN ( Kasus PT Bank "X" } - Hertanto, Hertanto; Santoso, Purbayu Budi (JURNAL BISNIS STRATEGI, 2000)
Recently, in the Indonesia economic crisis, banking became the first government priority since if was as a central point of economics. There are many policies to recover banking normally and reactivating the economic performances.The internal support of banking is needed to help government policy for banking recovery. To make it succeed, the company have to consider that human resource as the most important thing in a company. Human resource has competence to be developed, and the first step that have to be done is investment to the value, standard and behavior or firm belief to Increase the productivity. And this condition can be resulted through corporate culture.The objective of this research is to analyse the employees working productivity In the light of corporateculture. The problem from this research is corporate culture has not strong, because therre are different variance of culture strength and the low magnitude from corporate culture influenced toward work productivity. The purpose of this research is to analyze the culture strength, different variance due to inherited character, and the magnitude of corporate culture toward work productivity.